2022
DOI: 10.1097/jd9.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Depression and Quality of Life in Patients With Psoriasis

Abstract: Objective: To measure the prevalence of depression in patients with psoriasis and to evaluate the relationship between the severity of psoriasis and depression and its effect on patients' quality of life. Methods: A total of 154 patients with a confirmed diagnosis of psoriasis were assessed to determine the severity of psoriasis based on the psoriasis area and severity index score, presence, and severity of depression using the patient health questionnaire 9, and quality of life using the dermatology life qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[ 12 ] A prospective observational study from India also found a similar proportion of severe/very severe patients with PsO (37.7%). [ 14 ] Legs (69%), fingers (48%), scalp, knees, and neck (46% each) were the predominant sites involved in this analysis. These findings are in line with studies published across the Indian subcontinent, reporting lower limbs (78%),[ 11 ] trunk and limbs (70% each),[ 4 ] and scalp and extremities (74%),[ 15 ] as the most common sites of PsO in India.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 12 ] A prospective observational study from India also found a similar proportion of severe/very severe patients with PsO (37.7%). [ 14 ] Legs (69%), fingers (48%), scalp, knees, and neck (46% each) were the predominant sites involved in this analysis. These findings are in line with studies published across the Indian subcontinent, reporting lower limbs (78%),[ 11 ] trunk and limbs (70% each),[ 4 ] and scalp and extremities (74%),[ 15 ] as the most common sites of PsO in India.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, observational studies from India reported that PsO had a very-large effect on QoL in 34–35% of patients when determined through DLQI. [ 14 17 ] In contrast, a cross–sectional observational study from India found that PsO had a very-large effect on QoL in 70% of patients. [ 18 ] A prospective observational study from India including 154 patients with PsO found that 90.3% patients had depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although psoriasis is primarily a skin disease, it has been shown to influence the mental health impact of those affected. 1 , 2 , 3 Histologically, psoriasis is characterized by epidermal thickness and downward elongation of the rete ridges. The granular layer becomes thinner or disappears, capillaries elongate and dilate, and T cells enter the dermis and epidermis.…”
Section: Introductionmentioning
confidence: 99%